Fotografia: objeto ambíguo - estranhamento e desautomatização do olhar em Pedro Meyer - Ruza, João Carlos (2014)
This work aims to question the conception which deals with photography as a reliable and neutral register of reality. This is not a refuse of the documentary aspect of photography, neither its objective materiality, but rather the acceptance of photography as a image intrinsically ambiguous and polysemic, a codified representation of reality and so accept its symbolic character of object which needs to be deciphered in order to reveal its deepest meaning. For this, we use theoretical basis authors who, somehow, discuss critically the image; among them, Vilém Flusser, Hans Belting, Arlindo Machado and Joan Fontcuberta. Our findings were based on our professional practice that currently most of human measurements are made through images and that this relation not always are significantly satisfactory in a context of excess of images, particularly with regard to the above view which sees the photography as a simple reproduction and not a representation of reality, yet widely present. We think that is necessary a deconstruction of this view and the search of a richer approach related to photographic phenomenon as a whole. We use the proceed called estrangement, initially developed by the group known as Russian Formalists , as a possibility of a frame-braking approach in the relationship subject/image, aiming understand its meanings and practices, using as example its use in the analysis of the work of Mexican photographer Pedro Meyer, particularly his work called Heresias (2008)